Dienylation of Unfunctionalized Arenes with 1,6-Diynes via Rhodium-Catalyzed Directing-Group-Free C–H Bond Activation - Takahashi, Hiroto; Honjo, Yusaku; Shibata, Yu; Nagashima, Yuki; Tanaka, Ken (Synthesis, 2021)
It has been established that the dienylation of unfunctionalized arenes with 1,6-diynes, possessing aryl groups at the diyne termini, proceeds to give the corresponding dienylated arenes in the presence of a catalytic amount of an electron-deficient cyclopentadienyl rhodium(III) complex, [CpERhCl2]2, and a stoichiometric amount of silver carbonate. Experimental and theoretical mechanistic studies revealed that a CpERh(I) complex generated in situ might catalyze the present dienylation reaction.
Keywords: alkynes; dienylation; directing group-free C–H bond activation; rhodium; unfunctionalized arenes